Artificial Urinary Sphincter Is Better Than Slings for Moderate Male Stress Urinary Incontinence With Acceptable Complication Rate: A Systematic Review and Meta-Analysis - Lin, Lede; Sun, Wenjin; Guo, Xiaotong; Zhou, Liang (Frontiers in Surgery, 2022)
Background This meta-analysis aimed to compare the efficacy of artificial urinary sphincter (AUS) and slings for the treatment of moderate male stress urinary incontinence (SUI) based on existing data. Methods The study was in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analysis. We searched the widely acknowledged database including PubMed, Embase (Ovid version), Medline (Ovid version) and Cochrane Central Register of Controlled Trials (till February 2021). Male patients with moderate SUI who underwent AUS or slings procedure over 18 years old and had been monitored with mean follow-up time of at least 12 months were included. The primary outcome was success rate defined as daily pad use with 0-1 pad/d post-operatively. Articles with congruent outcomes were suitable for inclusion. Secondary outcome included complication rate of infection, erosion, acute urinary retention and surgical revision. Results Five studies with a total of 509 patients (295 for slings and 214 for AUS) were recruited. Success rate was higher in AUS with odds ratio (OR) =0.57 (95% confidence interval (CI): 0.36-0.90). As for overall complication rate, no significant difference was discovered between slings and AUS groups (OR=1.06, 95% CI: 0.58-1.92, P=0.86). Conclusions To conclude, AUS was better than slings for moderate male SUI treatment according to daily pad use with acceptable complication rate. Slings also had clinical value and were options when aging male patients were AUS naive and refused inserted mechanical devices. More higher-quality evidences are needed to confirm the efficacy of AUS and slings in moderate male SUI.